Trajectory planning of the humanoid manipulator - Kacprzak, C.; Pająk, Grzegorz (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents a method of planning a collision-free trajectory for a humanoid manipulator mounted on a rail system. The task of the robot is to move its end-effectors from the current position to the given final location in the workspace. The method is based on a redundancy resolution at the velocity level. In addition to this primary task, secondary objectives are also taken into account.
Keywords: humanoid manipulator; redundancy resolution; collision avoidance; manipulability measure